Efficacy of cetuximab in the treatment of squamous cell carcinoma. (October 2014) - Preneau, Sophie; Rio, Emmanuel; Brocard, Anabelle; Peuvrel, Lucie; Nguyen, Jean-Michel; Quéreux, Gaelle; Dreno, Brigitte
Background: Cutaneous squamous cell carcinomas (CSCC) are very common. Localized CSCC are cured by surgery and/or radiotherapy and have a better prognosis than locally inoperable advanced CSCC. Cetuximab has recently been proposed to treat locally advanced CSCC when surgery or radiotherapy cannot be offered. Objective: The authors report results of a pilot study conducted in inoperable CSCC patients treated with cetuximab alone or combined with chemotherapy or radiotherapy. Material and methods: This study was conducted in 20 CSCC patients. RECIST criteria were used to evaluate clinical and radiological responses. Results: Five patients received cetuximab associated with radiotherapy (CR), nine with carboplatin (CC) and six as monotherapy (CM) over 1-month cycle treatment. Response to treatment was evaluated every two cycles. After 2 months of treatment, the authors observed nine partial responses, six stabilizations and four progressions. Disease control rate was of 78% (100% for CR, 87.5% for CC and 50% for CM) with a 47% response rate (80% for CR, 37.5% for CC and 33% for CM). Conclusion: The authors confirm the potential interest of cetuximab to treat unresectable advanced CSCC alone or combined with CC and CM. These results justify discussing a further randomized study combining radiotherapy and cetuximab.